What Are Existing Structures in Communities for Physical Activity Promotion? A Comparative Case Study of Six Diverse Pilot Communities in Germany - Helsper, Natalie; Dippon, Lea; Kohler, Simone; Rütten, Alfred; Pfeifer, Klaus; Semrau, Jana (24th IUHPE World Conference on Health Promotion, 2022)
Background The German National Recommendations for Physical Activity (PA) and PA Promotion recommend community-based PA promotion with a focus on health equity. To support the effective and sustainable implementation of this approach at the local level, a co-produced six-phase action-oriented framework with nine key components was tested in six pilot communities (PC). These PC varied in terms of their type (urban, rural), region, readiness, and socioeconomic deprivation. As communities are complex systems with dynamic relationships and interactions, a deeper understanding of the community’s context is crucial for the implementation. Therefore, the aim of this study is to analyse the initial context including existing structures in the six diverse PC. Methods Using a comparative case study design, we conducted and transcribed verbatim in total 32 qualitative interviews with key stakeholders from each PC including 7 political stakeholders, 6 experts, 8 representatives of the administration, 5 “door-openers” with contact to people with social disadvantages and 6 community facilitators (one per PC). We used purposive sampling to identify interviewees in the PC. The development of the semi-structured interview guideline was based on the co-produced nine key components. Our analysis draws on the approach of the qualitative content analysis. Results We will structure our in-depth analysis through comparing similarities and differences in the contexts of the six PC along the following nine key components: “political support”, “integrating existing structures”, “cooperation and intersectoral partnership”, “participation”, “communication”, “competencies and qualification”, “strategic planning/methodical approach”, “infrastructural/financial/personal resources and timeframe”, and “offers/programs”. A first exploration of our available data revealed differences between rural and urban communities in the key components “policy support” and “integrating existing structures”. Discussion A thorough analysis of the initial community context will contribute to a better understanding of the relationships between the process, output, and outcome of community-based PA promotion. Finally, it will support an enhanced exploration of the impact of this approach regarding sustainable structural change for PA promotion at the community level and improvement of health equity. <